(untitled) - gary B Shelly ...[et al.] (Cambridge, Massachusetts, 2001)
The content of this book coversbasic through advanced JavaScript skills, including creating, writing, and reading cookies, writing HTML to frames and windows, table manipulation, array processing, and creation and manipulation of custom objects.
Keywords: javascript ( computer program language )